An Integrative Framework of Motivation in Islamic Education: Connecting Motivational Hadiths with Contemporary Educational Psychology Theories - Muhammad Aufa Ihsan (JURNAL ISLAM NUSANTARA, 2026)
Learning motivation remains a major challenge in education, particularly in integrating spiritual values with contemporary motivational approaches. This study aims to examine motivational messages contained in authentic hadiths and integrate them with modern educational psychology theories. A qualitative library research design was employed using Al-Lu’lu’ wal Marjan fī Ma Ittafaqa ‘Alayhi al-Shaykhan as the primary source, supported by scholarly literature on Self-Determination Theory, Growth Mindset Theory, Grit Theory, and Expectancy-Value Theory. Data were analyzed through thematic content analysis, comparative analysis, and integrative analysis. The findings identified three major motivational themes: patience in facing adversity, engagement in small but meaningful actions, and sincerity accompanied by consistency in good deeds. These themes correspond to Growth Mindset and Grit Theory, Expectancy-Value Theory, and Self-Determination Theory, respectively. The novelty of this study lies in proposing an integrative motivational framework that combines spiritual-transcendental values with empirical-psychological perspectives. The findings imply that Islamic education can strengthen student motivation through a holistic approach that integrates character, resilience, and intrinsic motivation.